Directions for Improving the Efficiency of Supply Chain Management Regulation of Health Care in Ukraine: A Case Study of Western European Countries - R.V. Shapoval; O.I. Demenko; K.V. Solntseva; A.S. Sydorenko (International Journal of Supply Chain Management, 2019)
In modern conditions Ukraine has a steady trend of high mortality rates caused by the low level of health care quality. In this regard, it becomes relevant to develop scientific approaches to improving the efficiency of administrative and legal regulation of the health service in the country. The article substantiates the main factors of the efficiency of the administrative and legal regulation of health care in Western Europe. The current state of the health service in Ukraine was analyzed. The key factors of the critical health care state in the country are identified. The expert evaluation technique was used to assess the efficiency of medical reform in Ukraine and to justify the main directions for improving the legal regulation of the health care service, taking into account the efficiency factors applied in Western Europe. A system of recommendations was developed for improving the legal framework of health care in Ukraine. The research results are practical in nature and will become the basis for the implementation of Ukraine’s European desire to strengthen the health care system and its potential, increase its safety and protect public health as a prerequisite for sustainable development and economic growth.